INTERACTIVE INSTRUCTION AS A POTENTIAL TOOL TO IMPROVE SPATIAL ABILITY OF LEARNERS - Sengupta, Aparajita; Upadhyaya, Himani (International Journal of Psychosocial Rehabilitation, 2020)
Instruction is an amalgamation of teaching as well as learning activities. The study aimed to find the effect of Interactivity with dynamic visualisation (IDV) of teaching chemistry; on Spatial Ability of Undergraduate (UG) boys & girls of Jabalpur, India. Random sampling was used with a total sample size of 315 UG students of Jabalpur. To measure the spatial ability of the UG students, Spatial ability test of DBDA Revised (David Battery of Differential Abilities) was used. The study was conducted by Experimental method. The researcher used Non-Equivalent Pre-test Post-test Control Group Design. Treatment was given for a period of one month to both the groups. The data was analyzed by Two way Analysis of Variance (ANOVA). A significant main effect was found for group as well as interactional effect between gender and group at 0.01 level of significance. Thus there is a need to bring focus on such innovative practices of teaching in chemistry education which can improve the spatial ability of the learners.